Numerical simulation of test particle diffusive shock acceleration in relativistic shocks with application to AGN 'central engines' - Quenby, J; Meli, A (2002)
Numerical modelling is performed for extreme relativistic parallel shocks with upstream Lorentz factors Gamma = 50. Assuming that the scattering is either large-angle or over pitch angles > Gamma(-1), spectral flattening and shock acceleration speed-up is found. The energy gain per cycle is similar to Gamma(2). The likely output from relativistic shocks due to the infall from the accretion disc to the AGN black hole is computed. Neutrinos from proton-gamma interactions may be detectable with planned neutrino telescopes but the gamma-ray output may contribute only 1/100th of the observed flux of 3C 273.